(untitled) (Delta Medical College Journal, 2025)
Background: Psoriasis is termed as hyperproliferative disease as epidermal basal cell exhibit increased frequency of mitosis in the disease. Although causes and pathogenesis of psoriasis remain unclear, a number of risk factors have been recognized. Several studies have demonstrated close association between psoriasis and serum calcium levels. Objective: The main objective of our study was to assess serum calcium level in patients suffering from psoriasis and find out its association with severity of psoriasis. Materials and method: A case control study was conducted in the department of Biochemistry, Nilphamari Medical College, Nilphamari, Bangladesh, from June 2021 to December 2021. The study enrolled 160 subjects of either sex with different age group from dermatology OPD. Among them 80 psoriatic patients were selected as cases and control group included 80 non-psoriatic patients with minor ailment. Results: Among 160 subjects participated, 90(56.25%) were female and 70(43.75%) were male. The mean age of the study group and of control group was 35.80±17.99 years and 37.65±15.70 years respectively. The mean serum calcium concentration was 9.08±0.26 mg/dL and 9.46±0.51 mg/dL in cases and controls respectively. The difference was statistically significant. Level of serum calcium was found significantly different among different groups of cases. Conclusion: Serum calcium level was significantly lower in patients of psoriasis compared to controls. Calcium concentration decreased significantly in more severe type of psoriasis. Delta Med Col J. Jan 2022;10(1): 10-13